Pendidikan Berbasis Multikultural melalui Kunjungan Tempat Ibadah pada Anak Usia 5-6 Tahun di TK Pembinaan Pasir Putih Pangkal Pinang - Haryantati, Wiji; Withasari, Yurinda (ICEJ : Islamic Childhood Education Journal, 2023)
The introduction of multiculturalism in early childhood is very important to train and build students' character so they are able to act democratically, humanistly and pluralistically in their environment. The methodology used in this research is descriptive qualitative. The data collection techniques use observation, interviews, documentation. The analysis technique used by researchers is through data reduction, data presentation, and drawing conclusions. The results of this research show that multicultural-based education through visits to places of worship for children aged 5-6 years includes three stages including: Planning stage, the teacher prepares everything that needs to be prepared for multicultural-based learning activities through visits to places of worship. In the second implementation stage, the teachers carried out as stated in the planning. In the third stage of evaluation, the teacher assesses by observing and taking notes and then adjusting to the aspects being assessed. With multicultural-based education through visits to places of worship for children aged 5-6 years, children can accept the differences that exist around them, such as differences in religion, social status or caste, race and culture. This research shows that multicultural-based education through visits to places of worship can develop from initially not yet developing to developing according to expectations.